A Case Study On Sime Darby Berhad (formerly Known As Synergy Drive Bhd) - Ng, Shir Lee (2009)
This case study, specifically though the study of the case of the recent M&A of Sime Darby Berhad ("SDB"), aims to examine SDB in executing M&A in theory, of which the rationale and reasonableness of value creation and synergistic potential from undertaking the M&A is to be examined and assessed.